NSM shear strengthening technique with CFRP laminates applied in high-strength concrete beams with or without pre-cracking - Barros, Joaquim A. O. (2012)
The effectiveness of the near surface mounted (NSM) shear strengthening technique with carbon fiber reinforced polymer (CFRP) laminates applied in high-strength concrete beams with a certain percentage of existing steel stirrups is assessed by experimental research. In this context, the influence of the following main parameters are investigated: (i) the percentage and the inclination of the CFRP laminates; (ii) the percentage of existing steel stirrups; (iii) the existence of cracks when the reinforced concrete (RC) beams are shear strengthened with NSM CFRP laminates. The results showed that the NSM shear strengthening technique with CFRP laminates is more effective when applied to RC beams of high-strength concrete, not only in terms of increasing the load carrying capacity of the beams, but also in assuring higher mobilization of the tensile properties of the CFRP. Inclined laminates were more effective than vertical laminates, and the shear resistance of the beams has increased with the percentage of laminates. Pre-cracked RC beams strengthened with NSM CFRP laminates have presented a load carrying capacity similar to that of the homologous uncracked strengthened beams.